Role of Leaders in Improving Employee Work Discipline PT. Coca Cola Amatil Indonesia (Ccai) Sorong Branch - Rosnani Rosnani; Agil Saeni; Miryam Diana Kalagison; Zulfachry Zulfachry (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
This study aims to determine the role of leadership in improving the work discipline of employees of PT. Coca Cola Amatil Indonesia Branch Sorong, research method using qualitative. Data collection techniques by observation, interviews, and documentation. Data analysis techniques, the data collected in this study, both primary data and secondary data were re-examined in order to determine the completeness of the data obtained. The results of this study indicate that the Role of Leaders in Improving Work Discipline of Employees of PT. Coca Cola Amatil Indonesia Sorong Branch, the Company aims to survive and achieve the expected profit in the future. Maintaining the viability of the company also means paying attention to and trying to guarantee and maintain a working workforce. Therefore, the role of a strong leadership figure is needed to answer the challenges that arise. exists, especially in business competition that demands various business competitiveness which will only appear new products in the competitive world of business, both in terms of strategy and in terms of implementation or operations, The role of leadership in increasing work discipline at PT Coca Cola Amatil Sorong branch is an important factor in the organization, because of the ability and skills of a leader in influencing his subordinates to achieve the goals achieved in an organization. The inhibiting factor in the implementation of PT Coca Cola Amatil Indonesia Sorong branch which can be an obstacle in realizing marketing strategies to increase sales volume is the obstacle that we always anticipate is the geographical location of West Papua with erratic weather in ordering products sometimes not on time to consumers, Efforts conducted by PT Coca Cola Amatil Indonesia, Sorong branch, one of the many companies in Sorong City that produce soft drinks. By recognizing competitors, the company can know where the position of its products is and wants to know what kinds of products are marketed and with careful strategy and planning, we continue to strive to enlarge our business in every City and Regency to compete with other businesses